The load-pull method of RF and microwave power amplifier design - Sevic, John (John Wiley & Sons, Inc., 2020)
"The book is intended for readers with an existing base of knowledge regarding the wireless power amplifier (PA), a key semiconductor component used in all wireless communication products. The PA influences battery-life, talk-time, cost, and size of wireless communication devices. The author presents a complete pedagogical design methodology for wireless PA design, from specification stage, to transistor selection, to final circuit design. An electrical engineer, having read the book, will be able to start with key specifications and end with a functioning wireless PA design to meet those specifications. This book fills an unmet need in the technical literature by describing a general, powerful, accessible method that spans multiple technology disciplines, including base-station, hand-set, sat-com, and military applications, all from a practical, hands-on perspective"--